2018
DOI: 10.1007/s00401-018-1899-7
|View full text |Cite
|
Sign up to set email alerts
|

DMD genomic deletions characterize a subset of progressive/higher-grade meningiomas with poor outcome

Abstract: Progressive meningiomas that have failed surgery and radiation have a poor prognosis and no standard therapy. While meningiomas are more common in females overall, progressive meningiomas are enriched in males. We performed a comprehensive molecular characterization of 169 meningiomas from 53 patients with progressive/high-grade tumors, including matched primary and recurrent samples. Exome sequencing in an initial cohort (n = 24) detected frequent alterations in genes residing on the X chromosome, with somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 60 publications
7
67
1
Order By: Relevance
“…Finally, while novel fusions were recently discovered in a subset of meningiomas, 26,27,33 we did not detect any clinically actionable gene fusions in the meningiomas in our study. This may be explained by the fact that the majority of the cases in our cohort have a low-grade histology, whereas gene fusions, such as those involving TERT (telomerase reverse transcriptase), have been described in high-grade meningiomas.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Finally, while novel fusions were recently discovered in a subset of meningiomas, 26,27,33 we did not detect any clinically actionable gene fusions in the meningiomas in our study. This may be explained by the fact that the majority of the cases in our cohort have a low-grade histology, whereas gene fusions, such as those involving TERT (telomerase reverse transcriptase), have been described in high-grade meningiomas.…”
Section: Discussioncontrasting
confidence: 75%
“…This may be explained by the fact that the majority of the cases in our cohort have a low-grade histology, whereas gene fusions, such as those involving TERT (telomerase reverse transcriptase), have been described in high-grade meningiomas. 27,33 Furthermore, while NF2 gene rearrangements have been reported in patients who received cranial irradiation in childhood, this group of patients was excluded in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Juratli et al . showed that TERT promoter mutations and RETREG1‐TERT rearrangement were present in recurrent meningioma samples, and TERT mutation predicted unfavourable clinical outcomes . Peyre et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, a detailed analysis was not performed in these earlier reports. Recently, using highthroughput sequencing, this genomic event has been identified to activate telomerase in many cancer types, including neuroblastoma, glioblastoma, meningiomas, malignant melanoma and pheochromocytomas, chromophobe renal cell carcinoma (ChRCC), HCC, and among others [71][72][73][74][75][76][77][78] (Fig. 3b).…”
Section: The Tert Gene Rearrangementsmentioning
confidence: 99%